High Red Meat Intake Exacerbates Dextran Sulfate-Induced Colitis by Altering Gut Microbiota in Mice - Li, Dan-ping; Cui, Min; Tan, Fang; Liu, Xiao-yan; Yao, Ping (Frontiers in Nutrition, 2021)
Inflammatory bowel disease (IBD) is a serious hazard to public health, but the precise etiology of the disease is unclear. High intake of red meat diet is closely related to the occurrence of IBD. In this study, we investigated whether the high intake of red meat can increase the sensitivity of colitis and the underlying mechanism. Mice were fed with different levels of red meat for 8 weeks and then the colonic contents were analyzed by 16S rRNA sequencing. Then 3% dextran sulfate sodium was used to induce colitis in mice. We observed the severity of colitis and inflammatory cytokines. We found that high-dose red meat caused intestinal microbiota disorder, reduced the relative abundance of Lachnospiraceae_NK4A136_group, Faecalibaculum, Blautia and Dubosiella, and increased the relative abundance of Bacteroides and Alistipes. This in turn leads to an increase in colitis and inflammatory cytokine secretion. Moreover, we found that high red meat intake impaired the colon barrier integrity and decreased the expression of ZO-1, claudin, and occludin. We also found high red meat intake induced the production of more inflammatory cytokines such as IL-1β, TNF-α, IL-17 and IL-6 and inflammatory inducible enzymes such as COX-2 and iNOS in dextran sulfate sodium-induced colitis. These results suggest that we should optimize the diet and reduce the intake of red meat to prevent the occurrence of IBD.